WEBINAR – MODERN MANAGEMENT METHOD - CLAUDIA ISAC (Annals of the University of Petrosani: Economics)
In this paper we have presented specific elements of using the webinar to support a business. After a brief presentation of the development of the Internet and IT technology, we have highlighted the need to use modern communication tools such as the webinar. Therefore, we have revealed the benefits of webinar implementation, especially in training or informing employees of companies with geographically dispersed locations, and a comparison with classical, frequently used methods. In the second part of the paper, after a classification of the webinars, we have showed some aspects of the operative management and the types of rooms used frequently for managerial communication and we have also indicated some functional aspects of the types of conference rooms from the simplest, organized through social networking to more complex rooms.